Functional evaluation of LTR-derived lncRNAs in porcine oocytes and zygotes with RNA-seq and small RNA-seq - Yang, Xu; Ji, Jingzhang; Cui, Hongdi; Zhao, Qi; Ding, Chunming; Xu, Chang (Frontiers in Genetics, 2022)
Long noncoding RNAs (lncRNAs) are increasingly being recognized as modulators of mammalian early embryonic development. However, in pig, it is seldom investigated. Here, to annotate full-length RNA transcripts, we performed the annotation by a new developed computational pipeline, termed RNA-seq and small RNA-seq combined strategy (RSCS), using our previously obtained RNA-seq and small RNA-seq data in porcine oocyte and zygote. Evidenced by the length comparison and the frequency of the core promoter and the polyadenylation signal motifs, the transcripts appear to be full-length. Furthermore, taking advantages of our strategy, we identified a large number of endogenous retrovirus-associated lncRNAs (ERV-lncRNAs), and found some of them were highly expressed in porcine zygote, comparing to oocyte. By the knockdown strategy, two ERV-lncRNAs TCONS_00035465 and TCONS_00031520 were identified to play a potential role in early embryo development of pig, laying a foundation for future research.